Settlement of Traffic Accident Cases Outside of Court in the Legal Area of Makassar Police - Lahaseng, Mas’ud (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study is a qualitative descriptive study that aims (i) To find out criminal acts, especially traffic accidents that do not have to be resolved through the courts (ii) To find out the police's considerations in mediating the perpetrators and victims of accidents and to find out whether the out-of-court settlement method is working well (iii) The method or method used by officers (Traffic Police) to resolve traffic accident cases outside the Court. The data collection method is through interviews and documentation and data analysis is carried out through data reduction, data display and data verification. The results of the study show (i) The settlement of traffic accidents outside the court by the police is a minor accident but does not result in serious injuries or even loss of life (ii) The settlement of traffic accidents outside the court by the police is considered better and more effective because it has a shorter process (iii) The method of settlement outside the court is P21, SP3, Diversion, ADR.